2017
DOI: 10.1016/j.jvoice.2015.12.020
|View full text |Cite
|
Sign up to set email alerts
|

Smartphones Offer New Opportunities in Clinical Voice Research

Abstract: Smartphone technology provides new opportunities for recording standardized voice samples of patients and sending the files by e-mail to the voice laboratory. This drastically improves the collection of baseline data, as used in research on efficiency of voice treatments. However, the basic requirement is the suitability of smartphones for recording and digitizing pathologic voices (mainly characterized by period perturbations and noise) without significant distortion. In this experiment, two smartphones (a ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 16 publications
3
36
0
7
Order By: Relevance
“…() used the same synthetic voice as in Manfredi et al . () and added external noise to the recordings. They found that for jitter measures and Noise to Harmonincs Ratio (NHR), good reliability remains up to ambient noise levels of 50 dB A .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…() used the same synthetic voice as in Manfredi et al . () and added external noise to the recordings. They found that for jitter measures and Noise to Harmonincs Ratio (NHR), good reliability remains up to ambient noise levels of 50 dB A .…”
Section: Discussionmentioning
confidence: 99%
“…, Manfredi et al . ). Both studies interpreted the plots visually but did not use the bias and limits of agreement in their assessment of agreement.…”
Section: Background and Motivationmentioning
confidence: 97%
See 1 more Smart Citation
“…1 In a first experiment, we demonstrated the reliability of smartphones with regard to quality of recordings over a wide range of degrees of deviance (perturbation and additive noise) and in the male and female ranges of fundamental frequency (F0) values. The comparison was carried out using realistic synthesized voice signals (sustained /a:/ altered by three levels of jitter and three levels of noise, the two basic acoustic voice quality parameters), which guarantee exact knowledge of reference values for voice quality parameters.…”
Section: Introductionmentioning
confidence: 99%
“…However, practical limits of tolerable ambient noise intensity values for the application considered here-that is, a patient recording his or her voice at home or at the workplace for sending to the voice clinic-are not accurately known. Furthermore, in our first paper, 1 only sustained /a:/ was used as voice material. It is thus worthwhile to assess the extent to which smartphones possibly distort synthesized samples comparable with natural voice productions, for which different reference values for F0 perturbation and noise to harmonics (N:H) ratio are exactly known.…”
Section: Introductionmentioning
confidence: 99%